2020
DOI: 10.21203/rs.3.rs-19071/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Importance of lipid ratios for predicting intracranial atherosclerotic stenosis

Abstract: Abstract Background: This study aims to investigate the association of lipid ratios with intracranial atherosclerotic stenosis (ICAS) in a Chinese population.Methods: This cross-sectional study included 658 consecutive patients with ischemic stroke. Intracranial and extracranial arteries were evaluated for atherosclerotic stenosis using digital subtraction angiography or computed tomography angiography… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that blood lipid indices, such as triglyceride/highdensity lipoprotein cholesterol (TG/HDL-C) ratio, apolipoprotein B/apolipoprotein A-I (Apo B/Apo A-I) ratio, total cholesterol (TC)/HDL-C ratio or low-density lipoprotein cholesterol (LDL-C)/HDL-C have a better predictive value of CAD than a single parameter (3)(4)(5)(6)(7)(8). Recent findings showed that blood lipid indices were significantly correlated with the risk of intracranial atherosclerotic stenosis and metabolic syndrome (9,10). The combination of lipid parameters represents relative status of blood lipids, which can comprehensively reflect the balance between atherosclerosis and anti-atherosclerosis and accurately assess lipid deposition (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that blood lipid indices, such as triglyceride/highdensity lipoprotein cholesterol (TG/HDL-C) ratio, apolipoprotein B/apolipoprotein A-I (Apo B/Apo A-I) ratio, total cholesterol (TC)/HDL-C ratio or low-density lipoprotein cholesterol (LDL-C)/HDL-C have a better predictive value of CAD than a single parameter (3)(4)(5)(6)(7)(8). Recent findings showed that blood lipid indices were significantly correlated with the risk of intracranial atherosclerotic stenosis and metabolic syndrome (9,10). The combination of lipid parameters represents relative status of blood lipids, which can comprehensively reflect the balance between atherosclerosis and anti-atherosclerosis and accurately assess lipid deposition (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that blood lipid indices, such as triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) ratio, apolipoprotein B/apolipoprotein A-I (Apo B/Apo A-I) ratio, total cholesterol (TC)/HDL-C ratio or low-density lipoprotein cholesterol (LDL-C)/HDL-C have a better predictive value of CAD than a single parameter [3][4][5][6][7][8]. Recent ndings showed that blood lipid indices were signi cantly correlated with the risk of intracranial atherosclerotic stenosis and metabolic syndrome [9][10]. The combination of lipid parameters represent relative status of blood lipids, which can comprehensively re ect the balance between atherosclerosis and anti-atherosclerosis and accurately assess lipid deposition [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that blood lipid indices, such as triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) ratio, apolipoprotein B/apolipoprotein A-I (Apo B/Apo A-I) ratio, total cholesterol (TC)/HDL-C ratio or low-density lipoprotein cholesterol (LDL-C)/HDL-C have a better predictive value of CAD than a single parameter [3][4][5][6][7][8]. Recent ndings showed that blood lipid indices were signi cantly correlated with the risk of intracranial atherosclerotic stenosis and metabolic syndrome [9][10]. The combination of lipid parameters represent relative status of blood lipids, which can comprehensively re ect the balance between atherosclerosis and anti-atherosclerosis and accurately assess lipid deposition [11][12].…”
Section: Introductionmentioning
confidence: 99%